Genetic instability of M protein and serum opacity factor of group A streptocci: evidence suggesting extrachromosomal control. - Cleary, P P (1975)
The M antigen, a primary determinant of virulence in group A streptococci that is expressed biologically as resistance to phagocytosis, is known to undergo a variety of phenotypic changes both in vivo and in vitro. These changes are nonrandom and can occur at a high frequency. Using the previously described relationship between the serum opacity reaction (associated with certain strains) and the presence of the M antigen, the phenotypic instability of the M antigen was analyzed. The results support the conclusion that M protein synthesis and the serum opacity reaction are directly or indirectly controlled by the same gene or by genes which are linked and can segregate as a unit. Moreover, growth conditions and the curing agents rifampin and ethidium bromide had a discernible influence on the segregation of clones unable to exhibit serum opacity factor and to resist phagocytosis by human leukocytes. Serial transfer of stationary-phase cultures of four strains of group A streptococci significantly increased the number of colonies negative for the serum opacity reaction and the M antigen. For two of four strains both ethidium bromide and rifampin also increased the segregation of colonies with this phenotype. In light of these experiments and the necessary controls, the possible influence of plasmids or bacteriophage in regulating M protein synthesis is discussed.